Intellectual property rights: Getting priorities right - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2015)
This paper stands in the nexus of trade policy and IPRs - and it aims to provide a different economic foundation for IPR policies by discussing how they are anchored in trade and economics. It is a "think piece" rather than a policy brief, and even if it comes with some policy recommendations, its core ambition is to revisit some key economic elements of IPRs and discuss them in a new light.
Keywords: 330